Determinants of Firm Value - Bella Rizkhyana; Shelly F. Kartasari; Shelfi Malinda (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: The purpose of this study was to examine the effect of gender diversity, intellectual capital, and corporate social responsibility on firm value using the perspective of Signalling Theory and Stakeholder Theory. Design/methodology/approach: This study uses secondary data from annual financial report. The research sample consisted of 88 observations collected on companies that entered LQ45 between 2017 and 2020. To conduct a test of the study's hypothesis using the Ordinary Least Squares (OLS) method. Eviews 20 were used to thes this research hypothesis. Findings: The results of this study indicate that gender diversity and corporate social responsibility have a significant effect on firm value, but intellectual capital has no effect on firm value. Research limitations/implications: The firm value will never cease to evolve to ensure the company's sustainability. Firm value serves as a standard for stakeholders when it comes to offering an overall assessment of the company. The more successful a business is in optimizing performance and paying attention to its internal and external environment, the higher the value. However, over the 2017-2020 period, the company's worth as assessed by PBV is likely to change. The increase and decrease in the firm's value are directly tied to the stock price; a high share price indicates a high firm value, and vice versa. Given these limits, it is proposed that future researchers study additional companies using a larger sample size and a longer time frame, as well as make observations using alternative proxies and include conditions on the firm's value before and during the COVID-19 period.